Vybrané atributy profesního sebepojetí českých novinářů [Professional Self-Image of the Czech Journalists: Selected Attributes] - Volek, Jaromír and Jirák, Jan (Mediální studia [Media Studies], 2006)
Habits, professional standards, routines, as well as the opinions of “press people” canoffer at least partial answers to questions dealing with journalists as aspecific socio-professional community. The article is based upon a survey of Czech journalists performed between the years 2003 and 2005 and its aim is to trace the basic types of their “professional self-definition”. The results suggest that along with traditional approaches of the journalistic profession (the “educational”, “advocate/adversarial” and “neutral/objective” types of journalists), there is a subgroup stressing a distinctive “career/pragmatic” approach to the role of being a journalist. Journalism is understood as an individual development tool, as a “fast track” towards an individual career (not only within the journalistic profession) by this subgroup.
https://katalog.adlr.link/Record/ai-53-152424